Examining Nigeria’s Digital Identity Project as Tool for Economic Inclusion and Regional Integration - Olaoluwa Faboye, Samson (African Human Mobility Review, 2022)
Access to the digitised economy has an increased penetration across the spectrum of Africa’s rural and urban population. In Nigeria, which is the context of this study, there is a long unsettling debate delineating citizens residing within any locality in Nigeria as ’indigenes’ or ’settlers’. This is at variance with the concept of ’transnational citizenship’, which confers rights to social inclusion in any individual’s nation-state. Digital identity registration becomes imperative to preserve social order and broaden the lines of inclusion for access to social services and monitoring access to the digital economy. The National Identity Number (NIN) is the digital identity for Nigerian citizens and residents, which can be leveraged for economic digitisation and regional and continental integration efforts. The research methodology employs descriptive and explanatory analysis of national, regional and continental policy frameworks applicable to Nigeria’s digital identity management systems. Boundaries of inclusion, transnational citizenship and the Westphalian Treaty of nation sovereignty form the theoretical underpinning of the study. This is used to present digital identity as a vital tool for socioeconomic inclusion, regional and continental integration. The case study of the Schengen Agreement as a successful integrative digital identity system fostering economic integration in Europe forms the basis of the recommendation. This calls for the ultimate use of digital identity to enhance international operable smart border practice, which would in turn guarantee border security while encouraging the desired free movement of persons and goods within the African continent KEYWORDS: citizenship, digitization, transnationalism